Globalization impact on interior space identity of cafes Baghdadi (Al-Academy, 2017)
Appeared in the light of globalization growing convergence of the distances between the countries in world, this convergence is causing mixing of cultures to become culture is a universal one culture, There are positives and negatives of this mixing and mingling of cultures, consider Loss of cultural identity is one of the biggest negatives the Arab cultural infrastructure in general and Iraq in special. In addition consider subject to not keep the cultural identity is the most important Arab issues and dangerous to our Arab identity in various fields, including design and architecture, highlights here the subject of research on the impact of globalization on the identity of the interior spaces, cafés of Baghdadi, one of the historical and cultural heritage and popular folklore, And linked to the history in the ancient city authentic because of its inherent historical, intellectual and cultural dimensions characterized by the acquisition of the fixed elements in the interior designs, which are accustomed to their boards Baghdadis, and the accommodation semi-house arrest of writers, artists, poets and gourmets singing and music. We find a vast difference between the new designs cafes than in the previous pretext keep pace with the development of civilization away from the cultural identity and cultural heritage of Iraq and keep the visual content inherent Baghdadi. The study consists of four chapters, the first chapter of the methodological framework speaks of search. While the second chapter explains the theoretical framework of the research included finding the concepts and definitions of some terms and a brief explanation of the elements of interior design, The third chapter covers research procedures supported by some design models, which have been analyzed and, finally Chapter IV research findings of the researcher through the analysis process, and with the conclusion and recommendations